Pengaruh Mental Accounting, Financial Self-Efficacy, Dan Financial Literacy Terhadap Perilaku Keuangan Generasi Z: Studi Empiris Pada Generasi Z di Kota Bogor - Muhammad Gilang Samudra; Yayuk Nurjanah (Jurnal Aplikasi Bisnis Kesatuan, 2026)
Financial behavior is a crucial aspect of Generation Z's lives, living in the digital era with easy access to various financial services and products. This convenience not only provides opportunities for financial management but also increases the risk of consumer behavior and unwise financial decision-making. Financial behavior is influenced by various factors, both psychological and cognitive, such as mental accounting, financial self-efficacy, and financial literacy. This study aims to analyze the influence of mental accounting, financial self-efficacy, and financial literacy on the financial behavior of Generation Z in Bogor City. The study used a quantitative approach with primary data obtained through questionnaires distributed to 106 respondents selected using a purposive sampling technique. Data analysis was performed using SPSS software through validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, partial (t) tests, simultaneous (F) tests, and coefficient of determination (R²) tests. The results indicate that mental accounting, financial self-efficacy, and financial literacy, both partially and simultaneously, have a positive and significant influence on the financial behavior of Generation Z in Bogor City. These findings indicate that the ability to manage finances, confidence in one's own financial capabilities, and a good level of financial literacy play an important role in shaping Generation Z's wiser, more disciplined, and more responsible financial behavior. Keywords : Mental Accounting, Financial Self-efficacy, Financial Literacy, Financial Behavior